Bipyridine bisphosphonate-based fluorescent optical sensor and optode for selective detection of Zn2+ ions and its applications. (20th April 2018) - Selva Kumar, R.; Ashok Kumar, S. K.; Vijayakrishna, Kari; Sivaramakrishna, Akella; Paira, Priyankar; Brahmmananada Rao, C. V. S.; Sivaraman, N.; Sahoo, Suban K.
Abstract : In this study, tetrabutyl 2, 2′-bisbipyridine-5, 5′-diylbis(methylene) diphosphonate (L ) as fluorescence optical sensor was developed for selective determination of Zn 2+ . Abstract : In this study, a bipyridine bisphosphonate-based tetrabutyl 2, 2′-bisbipyridine-5, 5′-diylbis(methylene) diphosphonate (L ) was developed as fluorescence optical sensor for sensitive and selective determination of Zn 2+ . The sensing ability ofL was investigated in solution as well as polymeric membrane phase using absorption and emission spectroscopy.L exhibits weak fluorescence in CH3 CN/H2 O (9 : 1, v/v). Upon interaction ofL with Zn 2+ ions, the emission intensity ofL significantly increases due to chelation-enhanced fluorescence (CHEF). The Job's plot and Benesi–Hildebrand (B–H) studies revealed the formation of aL –Zn 2+ complex in 1 : 1 binding stoichiometry with an estimated association constant of 4.2 × 10 3 M −1 . The complex formation betweenL and Zn 2+ was established from 1 H NMR, 31 P NMR, mass and theoretical studies. In order to make a low-cost and effective probe for sensing Zn 2+ in aqueous media, the optode was prepared by incorporatingL as a neutral ligand, dioctyl phthalate (DOP) as plasticizer, sodium tetraphenyl borate (NaTPhB) as an anionic additive and polyvinyl chloride (PVC) as supporting membrane. These components were systematically coated on a quartz plate of dimensions 12 mm × 16 mm with 5 mm thickness. After equilibration with Zn 2+, the optode exhibited a selective and strong fluorescence at 350 nm due to CHEF. The best performance of the optode was observed with a membrane havingL  : PVC : DOP : NaTPhB in proportions of 2 : 62 : 35 : 1 (w/w) in 4.5–8.5 pH range. The probe can detect Zn 2+ at concentrations as low as 1.3 nM with fast response time of 15 s and the optical response remains unaltered even after 3 months of use. The fluorescence reversibility ofL was studied by sequential addition of Zn 2+ and EDTA. The probe was used successfully used for determination of Zn 2+ in pharmaceutical and water samples. In addition, L was applied for Zn 2+ ions determination in HeLa cells using optical fluoroscence microscope.